2008
DOI: 10.1128/mcb.00477-08
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Polysome Assembly Enhances Imatinib Activity against Chronic Myelogenous Leukemia and Overcomes Imatinib Resistance

Abstract: Dysregulated mRNA translation is implicated in the pathogenesis of many human cancers including chronic myelogenous leukemia (CML). Because our prior work has specifically implicated translation initiation in CML, we tested compounds that could modulate translation initiation and polysomal mRNA assembly. Here, we evaluated the activity of one such compound, CGP57380, against CML cells and explored its mechanisms of action. First, using polysomal mRNA profiles, we found that imatinib and CGP57380 could independ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
53
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(57 citation statements)
references
References 37 publications
(51 reference statements)
4
53
0
Order By: Relevance
“…It also affects co-immunoprecipitation of phospho-eIF4E with MNK, which presumably reflects the presence of both entities in a complex with eIF4G (89). However, there are several studies showing no effect of inhibition of MNK activity on the level of eIF4G bound to eIF4E in cells (19,45,78,95). These discrepancies could be due to different degrees of MNK inactivation and/or higher cellular levels of eIF4G compared with eIF4E.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…It also affects co-immunoprecipitation of phospho-eIF4E with MNK, which presumably reflects the presence of both entities in a complex with eIF4G (89). However, there are several studies showing no effect of inhibition of MNK activity on the level of eIF4G bound to eIF4E in cells (19,45,78,95). These discrepancies could be due to different degrees of MNK inactivation and/or higher cellular levels of eIF4G compared with eIF4E.…”
Section: Discussionmentioning
confidence: 87%
“…To date, there have been numerous mRNAs identified as translationally regulated targets of MNK, including those encoding cytokines IL-17 (32) and pro-inflammatory TNF␣ (79), the anti-apoptotic protein Mcl-1 (28), ribosomal proteins S19 and L32 (19), proteins involved in cell proliferation (CDK2, CDK8, CDK9, HIF-1␣, KAP1, proliferating cell nuclear antigen, PIAS1, and RASSF1 (19)), proteins involved in cell cycle progression (cyclins A, B, D1, and D3 (19,78)), cancer-related proteins (HER2 (21), VEGF (35), and IRF-1 (84)), transcription factors (RFLAT-1 (46), CHOP (85), and ␤-catenin (25)), and neuronal proteins (Arc, ␣CaMKII, PKM-, calmodulin, BDNF (86), and PEM1 (20)). Translation of many of these mRNAs is also responsive to eIF4E levels, indicating a cap-and eIF4E-dependent mechanism of translation: HIF-1␣ (19), HER2 (21), Mcl-1 (28), cyclin D1 (87,78), VEGF (88), RFLAT-1 (46), ␤-catenin (25), and Arc (86). Recently, ribosomal profiling of IL-6-stimulated multiple myeloma cells revealed more than 160 mRNA targets that were translationally inhibited by expression of the phosphodefective eIF4E variant eIF4E(S209A) (89).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, although targeted mutations of the eIF4E S209 site significantly inhibit the transforming potential of eIF4E in NIH3T3 cells, it has not been shown whether using a targeted inhibitor of MNK1/2 has a similar effect (6). Furthermore, the MNK kinase inhibitor CGP57380 has shown limited antiproliferative efficacy in human chronic myelogenous leukemia; however, it does improve the antiproliferative and apoptotic effects of imatinib when used in combination (42). Although multiple MNK kinase inhibitors are available, no clinical trials are underway, at present, to test the efficacy of these compounds in human cancer.…”
Section: Eif4e-eif4g Interaction Inhibitor 4egi-1mentioning
confidence: 99%
“…Clinical examinations have revealed that Mnk1 is significantly elevated in human glioma tissues (18). Several studies have shown that the potent Mnk inhibitor CGP57380 suppresses human cancer cell growth in vitro (31,(37)(38)(39), but it remains unclear whether this inhibition is due to effects on Mnk1/2 or on Mnk1/2 plus other kinases promoting cell growth (40,41). To investigate the effects of specific Mnk inhibition in the context of human cancer, we set out to use an shRNAlentivirus system to stably knock down Mnk in human glioma cell lines.…”
Section: Mnk1/mnk2 Double Deficiency Does Not Affect Cellular Responsmentioning
confidence: 99%